The Influence of Digital Marketing, Word of Mouth On Purchasing Decisions At Umkm Bos Salad - Febriyanti, Shintia; Handayani, Tri (Inovbiz: Jurnal Inovasi Bisnis, 2024)
Bos Salad is one UMKM whose growth potential is faster than other UMKM in Bengkalis City. From the beginning of its establishment, Bos Salad has implemented a marketing strategy through Digital marketing and Word of mouth. The purpose of this study was to determine Digital marketing and Word of mouth on purchasing decisions at UMKM Bos Salad. This research is a type of quantitative research using primary data sources. The sampling technique used Accidental Sampling with a total of 100 respondents. Data collection using a questionnaire and analyzed using SPSS version 20 with Multiple linear Regression Analysis Test. The results showed that there is Digital marketing and Word of mouth on purchasing decisions at UMKM Bos Salad.